2016
DOI: 10.1103/physrevb.94.235119
|View full text |Cite
|
Sign up to set email alerts
|

Coupling quantum Monte Carlo and independent-particle calculations: Self-consistent constraint for the sign problem based on the density or the density matrix

Abstract: Quantum Monte Carlo (QMC) methods are one of the most important tools for studying interacting quantum many-body systems. The vast majority of QMC calculations in interacting fermion systems require a constraint to control the sign problem. The constraint involves an input trial wave function which restricts the random walks. We introduce a systematically improvable constraint which relies on the fundamental role of the density or one-body density matrix. An independentparticle calculation is coupled to an aux… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
80
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 56 publications
(87 citation statements)
references
References 48 publications
6
80
1
Order By: Relevance
“…It generalizes the method discussed in Ref. 40 under the ZT-AFQMC framework to finite temperatures. We will optimize the trial Hamiltonian (or trial propagator) step by step iteratively through a sequence of FT-AFQMC calculation so as to reduce the error from the constraint.…”
Section: B Ft-afqmc Calculations With Self-consistent Proceduresmentioning
confidence: 93%
See 1 more Smart Citation
“…It generalizes the method discussed in Ref. 40 under the ZT-AFQMC framework to finite temperatures. We will optimize the trial Hamiltonian (or trial propagator) step by step iteratively through a sequence of FT-AFQMC calculation so as to reduce the error from the constraint.…”
Section: B Ft-afqmc Calculations With Self-consistent Proceduresmentioning
confidence: 93%
“…In practice it is implemented approximately with a trial wave function or trial density matrix, which introduces a possible systematic bias in the numerical results but in turn removes the exponentially growing computational cost and recovers the algebraic complexity. Through many tests and developments in the last two decades [29][30][31][32][33][34][35][36][37][38][39][40][41] , the zero-temperature (ZT) CP-AFQMC method has been proved to be a highly accurate, general numerical approach for studying groundstate properties of various interacting fermion models as well as molecules and realistic materials by its generalization, the phaseless AFQMC method 28,42,43 .…”
Section: Introductionmentioning
confidence: 99%
“…The smaller differences in this regime tend to be more pronounced at shorter imaginary-times. A very interesting perspective will be the study of the possibility to use effective parameters [37] in the dynamical BCS theory to improve the agreement with exact results.…”
Section: Discussionmentioning
confidence: 99%
“…For general Hamiltonians, for instance the doped Hubbard model or realistic electronic Hamiltonians in solids or molecules, a constraint can be applied to control the sign or phase problem. This framework, even with simple trial wave functions to impose an approximate constraint, has been shown to be very accurate and has been applied widely in ground-state calculations [23][24][25][26][27][28][29][30][31]. Finitetemperature generalization of the approach has also been developed [32][33][34][35].These finite temperature calculations all have computational complexity of O(N 3 s ) [36], as they are formulated in the grand-canonical ensemble to analytically evaluate the fermion trace along each path in auxiliary-field space, leading to determinants with dimension N s .…”
mentioning
confidence: 99%